Comparative study of rapid and conventional tooling for plastics injection molding. Issue 2 (20th March 2017) - Mendible, Gabriel Antonio; Rulander, Jack A.; Johnston, Stephen P.
Abstract : Purpose: This study aims to evaluate the performance of injection molding inserts produced via rapid and conventional manufacturing techniques considering the mechanical and thermal performance of the tools as well as the resulting molded part quality. Design/methodology/approach: Three insert materials and manufacturing techniques were evaluated, jetted photopolymer (PolyJet) 3D printing using digital ABS, direct metal laser sintering (DMLS) using bronze and machining using stainless steel. Molding trials were performed, and the insert surface temperature, longevity and part properties were evaluated. Complementary information was acquired using computer simulation. Findings: Similar behavior and part quality were observed in machined and DMLS inserts. The latter were used for 500 cycles without any signs of failure. PolyJet inserts had increased cycle time and slower rate of cooling which increased shrinkage and crystallinity in the molded parts. PolyJet inserts could be produced quickly at a lower cost than machined or DMLS inserts. Research limitations/implications: Cooling within the insert was not studied; inserts were cooled indirectly by the mold plates behind them. Subsequent studies will incorporate cooling lines directly into the inserts. Originality/value: Little research has been done to understand the thermal behavior of inserts manufactured via rapid tooling techniques. This study provides a direct comparison between rapid tooling techniques, which is supported by simulation results and analysis of the actual molding properties.